Design of reactive-end DNA oligomers via incorporation of oxanine into oligonucleotides using terminal deoxynucleotidyl transferase. (November 2017) - Jang, Eui Kyoung; Ki, Mi-Ran; Pack, Seung Pil
Graphical abstract: Highlights: Deoxynucleotide triphosphate of oxanine (dOTP) was testified as a new substrate for TdT. TdT-mediated incorporation of oxanine (Oxa) was optimized to design Oxa-labeled DNA. Oxa-labeled DNA oligomer can react with polyamines under physiological conditions. This is a new enzymatic methods for preparation of reactive Oxa-labeled DNA oligomers. Abstract: Oxanine (Oxa, O), a modified nucleobase, has a novel O-acylisourea structure. Oxa-incorporated oligodeoxynucleotides (ODNs) are reactive DNA oligomers that permit conjugation with various nucleophilic molecules in an activation-free manner. In this study, we developed a new procedure for enzymatic preparation of reactive-end DNA oligomers, using terminal deoxynucleotidyl transferase (TdT), in which a reactive Oxa base is incorporated into the 3′-end of ODNs. One limitation of TdT, an enzyme widely used for end labeling of DNA oligomers, is that it is difficult to control the number of incorporated labels, because it shows template-independent extension with random nucleotides. Notably, TdT showed a rate and efficiency of incorporation of the modified nucleobase, Oxa, different from that of natural bases. We investigated the conditions of TdT-mediated DNA incorporation of Oxa and achieved incorporation of Oxa at the 3′-end of ODNs by optimizing reaction parameters such as temperature and enzyme, cofactor, and substrate concentrations. We also confirmed the reactive functionality of Oxa after incorporation into ODNs by amide bonding conjugation with a polyamine (spermine) under physiological conditions, without need for an additional activation step.